A PLCS framework for PDM/ERP interoperabilty. (20th October 2011) - Paviot, Thomas; Cheutet, Vincent; Lamouri, Samir
Wide diffusion of methodologies and software relevant to product lifecycle management (PLM) in industrial companies faces heterogeneity of information technology (IT) systems. Especially, the lack of interoperability between product data management (PDM) systems, that drive virtual product development, and enterprise resource planning (ERP), which manages real product, cannot lead to a global description of the product development process. We demonstrate that a mediator approach is pertinent for the coordination of these two systems. The use of open standards, and more precisely STEP Application Protocol 239, known as product lifecycle support (PLCS), allows overcoming issues related to semantic part of this interoperability. The last part of the study focuses on implementation issues, in order to develop an interoperability framework based upon a consistent product data model, whether the viewpoint is from the design or logistics businesses.